An Exploration of Lifting and Low Back Pain in Manual Workers - Saraceni, Nicholas Anthony (Curtin University, 2021)
There are strong beliefs in society and in healthcare about how to prevent and manage lifting-related low back pain. The results of the studies within this thesis suggest that there is no good evidence to support the current lifting paradigm. The evidence within this thesis suggests that lifting-related low back pain should be viewed as a multi-dimensional and complex phenomena, where both biomechanical and non-biomechanical factors may uniquely influence each individual.